Progress Report to The IMFC on The Activities of The Independent Evaluation Office of The IMF. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2022)
Since the 2021 Annual Meetings, the IEO has made considerable progress with three ongoing evaluations, while two management implementation plans (MIPs) to follow up on recommendations from previous evaluations have been approved by the Board. In addition, to mark its twentieth birthday, the IEO organized a virtual conference to reflect on experience from its second decade and consider future challenges. We have also contributed to the ongoing work on institutional integrity at the IMF, drawing on a stocktaking of material contained in past evaluations and are considering additional work on these issues as we select two new evaluation topics later this year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Money and Monetary Policy; Political Economy